Computer Applications for Communication, Networking, and Digital Contents International Conferences, FGCN and DCA 2012, Held as Part of the Future Generation Information Technology Conference, FGIT 2012, Gangneug, Korea, December 16-19, 2012. Proceedings - Kim, Tai-hoon.; Ko, Dae-sik.; Vasilakos, Thanos; Stoica, Adrian; Abawajy, Jemal; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume constitutes the refereed proceedings of the International Conferences, FGCN and DCA 2012, held as part of the Future Generation Information Technology Conference, FGIT 2012, Kangwondo, Korea, in December 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of future generation communication and networking, and digital contents and applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Software Engineering; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval